Cell-Type–Specific, Ketohexokinase-Dependent Induction by Fructose of Lipogenic Gene Expression in Mouse Small Intestine. Issue 7 (9th May 2020) - Al-Jawadi, Arwa; Patel, Chirag R; Shiarella, Reilly J; Romelus, Emmanuellie; Auvinen, Madelyn; Guardia, Joshua; Pearce, Sarah C; Kishida, Kunihiro; Yu, Shiyan; Gao, Nan; Ferraris, Ronaldo P
ABSTRACT: Background: High intakes of fructose are associated with metabolic diseases, including hypertriglyceridemia and intestinal tumor growth. Although small intestinal epithelia consist of many different cell types, express lipogenic genes, and convert dietary fructose to fatty acids, there is no information on the identity of the cell type(s) mediating this conversion and on the effects of fructose on lipogenic gene expression. Objectives: We hypothesized that fructose regulates the intestinal expression of genes involved in lipid and apolipoprotein synthesis, that regulation depends on the fructose transporter solute carrier family 2 member a5 [ Slc2a5 (glucose transporter 5)] and on ketohexokinase ( Khk ), and that regulation occurs only in enterocytes. Methods: We compared lipogenic gene expression among different organs from wild-type adult male C57BL mice consuming a standard vivarium nonpurified diet. We then gavaged twice daily for 2.5 d fructose or glucose solutions (15%, 0.3 mL per mouse) into wild-type, Slc2a5 -knockout (KO), and Khk -KO mice with free access to the nonpurified diet and determined expression of representative lipogenic genes. Finally, from mice fed the nonpurified diet, we made organoids highly enriched in enterocyte, goblet, Paneth, or stem cells and then incubated them overnight in 10 mM fructose or glucose. Results: Most lipogenic genes were significantly expressed in the intestine relative to the kidney, liver, lung, and skeletal muscle. In vivo expression of Srebf1, Acaca, Fasn, Scd1, Dgat1, Gk, Apoa4, and Apob mRNA and of Scd1 protein increased ( P  < 0.05) by 3- to 20-fold in wild-type, but not in Slc2a5 -KO and Khk -KO, mice gavaged with fructose. In vitro, Slc2a5 - and Khk -dependent, fructose-induced increases, which ranged from 1.5- to 4-fold ( P  < 0.05), in mRNA concentrations of all these genes were observed only in organoids enriched in enterocytes. Conclusions: Fructose specifically stimulates expression of mouse small intestinal genes for lipid and apolipoprotein synthesis. Secretory and stem cells seem incapable of transport- and metabolism-dependent lipogenesis, occurring only in absorptive enterocytes.